Traveling on a Train : 2-D Shapes - Barchers, Suzanne (Huntington Beach, Calif. : Teacher Created Materials, 2011)
Trains take you where you need to go and they move food and other goods from one place to another. Trains are full of shapes, too, which make them fun to look at. You can find circles on the train's wheels and rectangles on the railroad tracks and railroad signs. There are even shapes at the train station. Some ceilings have circles or triangles and some floors have squares. Look inside. Can you find any more?
Includes index and answer key
Keywords: Shapes -- Juvenile literature; Two-dimensional shape -- Juvenile literature